2011
DOI: 10.1097/jto.0b013e3182011f70
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Presence of Microscopic Vascular Invasion After Complete Resection of Stage I–II pT1-T2N0 Non-small Cell Lung Cancer and Its Relation with T-Size Categories: Did the 2009 7th Edition of the TNM Staging System Miss Something?

Abstract: The finding of MVI in pT1-T2N0 NSCLC is frequent. MVI correlates with adenocarcinoma histotype, increased tumor dimensions, and tumor-infiltrating lymphocytes. The presence of MVI is an independent negative prognostic factor. In our experience, MVI was a stronger prognostic indicator than T size in T1a-T2b categories according to the 2009 TNM staging system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 31 publications
(42 reference statements)
0
36
0
4
Order By: Relevance
“…Although results correlating angioinvasion and a poor outcome in early stage lung cancer have been inconsistent [4,5] several recent pathological studies have identified a strong association [6][7][8][9]. The PI3K/mTOR pathway has been linked to invasion through the upregulation of MMP-9 in hepatocellular carcinoma [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although results correlating angioinvasion and a poor outcome in early stage lung cancer have been inconsistent [4,5] several recent pathological studies have identified a strong association [6][7][8][9]. The PI3K/mTOR pathway has been linked to invasion through the upregulation of MMP-9 in hepatocellular carcinoma [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore vascular invasion, along with other published studies [25][26][27][28], in our large series resulted as another strong independent prognostic factor. Although prospective studies are needed, our findings underline the importance of a careful evaluation of lymph nodes and vascular invasion in resected NSCLC as it may provide additional useful information for identifying patients who are at high risk and who may be candidates for further medical treatment after or before surgery.…”
Section: Discussionmentioning
confidence: 51%
“…The most complex and unsatisfactory aspect of the current TNM staging system in lung cancer is represented by the method of assessing nodal disease. In lung cancer the anatomic extent of lymph node metastasis defines pN categories [12,28]. This current nodal system, based only on the anatomic extent of metastatic lymph nodes, can result in different prognosis even in the same nodal stage, especially with mediastinal (N2) lymph node involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted on lymphnode-negative early-stage patients that had been subject to resection, Naito et al established that MVI was observed to be an independent negative prognostic factor and found as a stronger prognostic indicator than T size, according to the 2009 TNM staging system [21]. Likewise Ruffini et al worked with patients diagnosed with NSCLC and operated in pT1-T2N0 stages and found that the presence of MVI was an independent negative prognostic factor [22]. However, Chandrachud et al found in a survival analysis performed on operated NSCLC patients that tumor volume was the only factor affecting survival, the authors identified vascular invasion not to be a determining value in prognosis [23].…”
Section: Discussionmentioning
confidence: 99%